Anatomic Site Based Ploidy Analysis of Oral Premalignant Lesions - Islam, M. N. (Humana Press Inc, 2009)
The location of oral leukoplakia correlates strongly with the probability of finding dysplastic or malignant alterations at biopsy. It is well established that early detection can dramatically improve the 5-year survival rates for oral squamous cell carcinomas. Since aneuploidy is predictive of future conversion to malignancy, we hypothesized that dysplastic lesions from high-risk sites (floor of mouth, tongue and lips) would exhibit greater aneuploidy than low-risk sites (palate, gingiva and buccal mucosa). Epithelial sections from 60 archival samples diagnosed as mild dysplasia (36 females, 20 males) from various high/low risk locations were stained with Blue Feulgen Stain for DNA Ploidy Analysis (Clarient, Aliso Viejo, CA) and ploidy was analyzed using a ChromaVision ACIS II (Clarient, ALiso Viejo, CA) Image cytometry system. A DNA histogram was generated using an image analyzing software that evaluated the amount of Feulgen stain which is proportional to the amount of nuclear DNA. An ANOVA analysis followed by the Student’s‘t’ test revealed significant differences between means (P ≤ 0.05). Lesions originating from lateral/ventral tongue (85%), floor of mouth (50%) and soft palate (44%) exhibited a higher frequency of aneuploidy than lesions from gingiva (22%) and lower lip (25%). This pilot study demonstrates that dysplastic lesions from high-risk sites such as the floor of the mouth and lateral/ventral tongue have higher frequency of aneuploidy.